A transparência dos Bancos de Desenvolvimento e das Agências de Fomento do Brasil - Goncalves, Barbara Garschagen (2022)
As public institutions whose development activities are carried out, mainly, from the management of public funds and amounts transferred by state governments, it is up to Development Banks (BD) and Development Agencies (AF) to assume conduct that prioritizes the quality of their practices of transparency and accountability, contributing to the inspection of both external control and society itself. In this sense, guided by a script of observations based on the BNDES' Transparency Guide, the present study proposed to carry out a diagnosis of the active transparency of BD and AF in activity in Brazil. It was sought to verify how is the transparency of these institutions with regard to the allocation of public resources under their management and the processes of credit operations carried out. Still, the option for the analysis of two different types of public development institutions allowed to verify if the current transparency guidelines of the AF - created during the redemocratization of Brazil - are more advanced than those verified in the BD - created during the Military Regime in the country. The observation protocol consisted of 33 (thirty-three) items distributed among 8 (eight) pillars, namely: Policies and guidelines; Institutional; Finance and jobs; Portfolio information; Customer data; Operations data; Impact; and Social Participation. Data collection took place through direct consultation on the website of each institution in the sample. The results show that, in terms of transparency, the BD and AF in Brazil are similar, but still insufficient. The reality found in institutional portals is marked by the absence of important information, which would clarify the criteria used to define the allocation of state funds. Among the available information, most only aim to comply with the rules imposed by current legislation. In view of the facts raised, it becomes evident the need to make all information related to the operations carried out by the BD and AF available for public access, in order to allow effective monitoring and control of the management of public resources